2018
DOI: 10.1542/peds.2017-2426
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for Suicide Ideation or Attempt: 2008–2015

Abstract: Encounters for SI and SA at US children's hospitals increased steadily from 2008 to 2015 and accounted for an increasing percentage of all hospital encounters. Increases were noted across all age groups, with consistent seasonal patterns that persisted over the study period. The growing impact of pediatric mental health disorders has important implications for children's hospitals and health care delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
256
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(283 citation statements)
references
References 51 publications
23
256
0
4
Order By: Relevance
“…5 Similarly, administrative data in the United States show that presentations to hospital for suicidal ideation or attempts among children and adolescents almost doubled between 2008 and 2015, with the highest increase for adolescent girls. 6 Self-poisoning rates among 10-to 18-year-olds, which had declined in the US since the turn of the century, increased substantially from 2011 to 2018, primarily among girls. 7 Surveys of high school students in the US have shown a similar pattern for self-reported symptoms of depression, major depressive episodes and suicidality over the last 2 decades.…”
mentioning
confidence: 99%
“…5 Similarly, administrative data in the United States show that presentations to hospital for suicidal ideation or attempts among children and adolescents almost doubled between 2008 and 2015, with the highest increase for adolescent girls. 6 Self-poisoning rates among 10-to 18-year-olds, which had declined in the US since the turn of the century, increased substantially from 2011 to 2018, primarily among girls. 7 Surveys of high school students in the US have shown a similar pattern for self-reported symptoms of depression, major depressive episodes and suicidality over the last 2 decades.…”
mentioning
confidence: 99%
“…; Plemmons et al . ). These statistics represent a high‐risk population, particularly when a suicide attempt is a key risk factor for death by suicide (Goñi‐Sarriés et al .…”
Section: Introductionmentioning
confidence: 97%
“…One Canadian study sample found that 87% of admitted adolescents had thoughts of injuring themselves prior to admission, 77% did engage in nonsuicidal self-injury (NSSI), and 67% had made an attempt to end their life prior to admission (Preyde et al 2014). This is recognized internationally with an increasing number of adolescents admitted to inpatient care with suicidal ideation, attempts, and NSSI (Esposito-Smythers et al 2006;Hanssen-Bauer et al 2011;Plemmons et al 2018). These statistics represent a high-risk population, particularly when a suicide attempt is a key risk factor for death by suicide (Goñi-Sarri es et al 2018;World Health Organization 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, suicide rates have tripled in this age group (Curtin, Hedegaard, Minino, & Warner, 2016). Hospitalizations for SI and behavior among youth have also doubled over the last 10 years (Plemmons et al, 2018) but clinical trials for adolescent suicidal behavior are limited (Ougrin, Tranah, Stahl, Moran, & Asarnow, 2015). Below we review randomized trials of in-person outpatient treatments for suicidal adolescents with or without nonsuicidal self-injury (NSSI) that report these specific outcomes.…”
Section: Introductionmentioning
confidence: 99%